Habitat occupancy of terrestrial mammals along Singapore’s purpose-built wildlife corridor - Sivaraman Sivanantham (Nanyang Technological University, 2021)
Habitat fragmentation has been intensely researched due to its effect in undermining the integrity of whole ecosystems and ultimately resulting in the decline of biodiversity. Construction of Bukit Timah Expressway in Singapore (1986) placed a physical barrier between Bukit Timah Nature Reserve and Central Catchment Nature Reserve resulting in the fragmentation of these habitats that were connected. Eco-Link@BKE, a purpose-built wildlife corridor was constructed in 2013 to restore the connectivity, facilitating the safe passage of terrestrial animals across. This study quantified the habitat use of nine species of animals in the two forest patches, observed through camera traps across 2,641 trap nights via single-species, single-season occupancy modelling. In addition, the influence of increasing independence between sampling sites on goodness-of-fit of occupancy modelling was investigated. Findings highlighted that occupancy of Macaca fascicularis (long-tailed macaque) and Sundasciurus tenuis (slender squirrel) differed across sites. Occupancy modelling could not be carried out for seven mammalian species due to poor goodness-of-fit results. This paper also explored the possible reasons for the poor model fit and future measures that would allow for an effective sampling design to better improve occupancy modelling.